Comparing qualitative and quantitative echocardiographic markers to assess cardiac contractility in newborn infants: protocol for a prospective cohort study - Sujith Pereira; Saulius Satas (BMJ Paediatrics Open)
Introduction Neonatologist-performed echocardiography (NPE) is increasingly used in the neonatal intensive care unit, aiding clinicians in enhancing diagnostic precision and guiding treatment decisions based on underlying pathophysiology. Experienced NPE operators typically use visual estimation of the cardiac contractility and if required confirm findings using quantitative echocardiographic markers.While various quantitative echocardiographic markers are available to assess left and right ventricular contractility, this study aims to compare the proficiency of NPE-experienced and non-experienced providers in accurately assessing cardiac contractility using a combination of commonly used qualitative and quantitative echocardiographic markers.Methods and analysis Newborn infants, both inborn and outborn, undergoing routine NPE by the authors at Homerton University Hospital and Aberdeen Maternity Hospital from 1 April 2024 to 1 October 2024 will be studied. Indications for NPE include murmur evaluation, infants receiving intensive care and the need to assess underlying cardiovascular physiology.Blinded experienced and non-experienced NPE operators will independently assess left and right ventricular contractility using qualitative echocardiographic markers. The results will be compared with standard quantitative echocardiographic markers for cardiac contractility, and reliability studies will also be conducted for quantitative makers.Clinical data will be sourced from electronic patient records and national neonatal database. Sensitivity, specificity, positive predictive and negative predictive values, and positive and negative likelihood ratios will be calculated.Ethics and dissemination The study is approved by the Health and Care Research Wales Research Ethics Committee and the Health Research Authority (HRA) (reference 23/HRA/3066). The study findings will be presented at national/international conferences and published in peer-reviewed scientific journals.